Motivasi Belajar Siswa Sekolah Dasar Di Kota Magelang - Indah, Martia Yosi Nurfa; Yanti, Maya Mardi; Arifi, Yollawati; Pawestri, Ade Ayu Mutiara; Hermahayu, Hermahayu (Jurnal VARIDIKA, 2020)
Student learning motivation refers to how students get the urge to learn. Learning motivation can be obtained from three aspects, namely extrinsic, intrinsic, and combination motivation. This study aims to determine the analysis related to how the level of motivation for elementary school student learning is influenced by intrinsic factors, extrinsic factors, as well as a combination of both factors. The method used in this research is descriptive quantitative, with data collection methods that refer to the Scale of Intrinsic versus Extrinsic Orientation in The Classroom (Susan Harter's Intrinsic Orientation Scale in Classes) owned by Susan Harter in 1981. Based on the analysis using the SPSS program, as many as 50 , 4% (57 students) of 113 elementary school students in Magelang City had a high level of motivation to learn combination. While the remaining 49.6% (35 students) are divided into categories of extrinsic learning motivation categories, namely 31% of 113 students, and 18.6% (21 students) of 113 students have a tendency for intrinsic learning motivation.